Influence of dry season supplementation for cattle on soil fertility and millet (Pennisetum glaucum L.) yield in a mixed crop/livestock production system of the Sahel - Sangare, M.; Fernández Rivera, S.; Hiernaux, Pierre H.Y.; Bationo, B. André; Pandey, V.S. (Springer, 2002)
An experiment was conducted in 1996 and 1997 in semi-arid Niger, to determine the influence of supplementation (no supplement, millet bran + simple superphosphate, or millet bran + simple superphosphate + blood meal) for cattle and mulching (0 or 3 t ha-1 of Aristida sieberiana straw) on soil fertility and millet yield. Manure was applied through corralling at a rate of 3 t faecal dry matter (FDM) ha-1 alone or associated with mulching. The residual effects of the treatments were measured on a second millet crop in 1997. Compared to control, the association of mulching and corralling of supplemented as well as non supplemented cattle increased soil pH (KCI) (P < 0.01), Bray1-P (P < 0.05) and NH4-N (P < 0.05); grain by 136 % (P < 0.01) stover yield by more than 150 %a (P < 0.05); and N and P uptake (P < 0.01) during the two cropping seasons. The association of mulching and corralling increased soil NH4-N (P < 0.01) and soil pH (P < 0.01), compared to the sole corralling. The improvement of soil chemical properties resulted in grain yield increases of 54 % (P < 0.01) and stover increases of 42 % (P < 0.01). The associated effect of mulching and corralling on grain and stover yield was higher when cattle were supplemented (67 and 50 %) than when they were not supplemented (30 and 26 %). The effects of the supplementation on grain and stover yields, and N and. P uptake by millet were low, when animals were corralled on bare soil (no mulching). There were no residual effects of supplementation on soil fertility and crop yield.